Strategi Komunikasi Persuasif Iklan Pinjaman Online "Adakami - TVC - #AdakepastianAdaKami" di YouTube - Pradipta, Alfred; Sukendro, Gregorius Genep (Kiwari, 2025)
This study aims to analyze persuasive communication strategies in the online loan advertisement “Adakami - TVC - #AdakepastianAdaKami” published on YouTube. The background of this research lies in the growing presence of online loan advertisements on digital platforms, along with the success of Adakami’s advertisement, which went viral and gained more than seven million views. The study focuses on how the advertisement employs persuasive communication techniques to influence consumer perceptions and decision-making. This research adopts a descriptive qualitative method, with data collected through in-depth interviews and observations. The informants consist of several viewers of the Adakami advertisement on YouTube and an expert in the field of digital creative. The data were analyzed to explore experiences, interpretations, and audience perceptions of the conveyed message. The findings indicate that the Adakami advertisement successfully delivers persuasive messages through the use of appealing visuals, clear text, and positive emotional reinforcement. The advertisement also applies key principles of persuasive communication, including selective exposure, audience participation, inoculation, and magnitude of change. Audience feedback further demonstrates that the advertisement effectively enhanced public awareness and interest in Adakami’s online loan services. Penelitian ini bertujuan menganalisis strategi komunikasi persuasif dalam iklan pinjaman online “Adakami - TVC - #AdakepastianAdaKami” yang ditayangkan di media sosial YouTube. Latar belakang penelitian ini adalah semakin maraknya iklan pinjaman online pada platform digital, serta keberhasilan iklan Adakami yang menjadi viral dengan capaian lebih dari 7 juta tayangan. Fokus penelitian diarahkan pada upaya iklan tersebut dalam memengaruhi persepsi dan keputusan konsumen melalui teknik komunikasi persuasif. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam dan observasi. Informan terdiri atas sejumlah penonton iklan Adakami di YouTube serta seorang ahli di bidang digital creative. Data yang diperoleh dianalisis untuk memahami pengalaman, interpretasi, serta persepsi audiens terhadap pesan yang disampaikan. Hasil penelitian menunjukkan bahwa iklan Adakami mampu menyampaikan pesan persuasif secara efektif melalui kombinasi visual yang menarik, teks yang jelas, dan penguatan emosi positif. Iklan ini juga menerapkan prinsip-prinsip komunikasi persuasif, antara lain pemaparan selektif, partisipasi khalayak, inokulasi, serta besaran perubahan. Umpan balik dari audiens mengindikasikan bahwa iklan tersebut berhasil meningkatkan kesadaran dan minat masyarakat terhadap layanan pinjaman online Adakami.